Outcome and Owner Perception of Conservative and Surgical Management of Fracture of the Ulna in 20 Horses. (September 2015) - Ladefoged, S.; Wallin, J.; Toth, T.; Andersen, P.H.
Abstract : Reasons for performing study: While open reduction and internal fixation is the treatment of choice for most ulnar fractures conservative treatment is sometimes chosen due to financial constraints. Additional motives for the choice of treatment may be present, and the clients perception is therefore of interest. Objectives: To compare survival and outcome between horses treated for an ulnar fracture, either surgically or conservatively and to assess clients perception of treatment. Study design: Retrospective study. Methods: Medical records and radiographs of horses treated between January 2002 and December 2012, with a diagnosis of ulnar fracture were reviewed. Information regarding short‐ (within 1 year) and long‐term (>1 year) outcome and owner satisfaction with treatment was obtained via telephone questionnaires. Differences between groups were investigated using a chi‐square or Fisher's exact test. Results: Fracture types included 11 type 4, 7 type 5, one type 2, and one type 1b fracture. Eleven horses were treated surgically ( Group 1 ). Nine horses were managed conservatively ( Group 2 ). Group 1 : 7/11 (64%) survived >1 year, 5/11 (45%) returned to previous athletic level. In Group 2 : 6/9 (67%) survived >1 year, 4/9 (43%) returned to previous athletic level. No significant difference in outcome could be detected. There was no difference in the total treatment cost for horses that stayed at the hospital (P = 0.22). Owners in Group 1 expressed more satisfaction with the treatment than owners in Group 2 . Several of the latter expressed welfare concerns regarding the prolonged stall confinement in harness involved with this treatment. Conclusions: Veterinarians recommending therapy for cases of ulnar fractures should be aware that many can be treated surgically with a good outcome. Prolonged hospitalisation and stall confinement of horses treated conservatively was a major welfare concern of the owners interviewed and had the same total cost as surgical treatment. Ethical animal research:  Ethical review not currently required by this conference: retrospective clinical study. Explicit owner informed consent for inclusion of animals in this study was not stated.Source of funding:  None.Competing interests:  None declared.